2011
DOI: 10.1590/s0100-83582011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Corn growth and yield in competition with weeds

Abstract: -Although labor is intensive, evaluating the growth of crops may allow a better understanding of crop performance, including the reasons why certain cultivars can compete better with weeds. This study aims at evaluating growth, green ear yield, and grain yield in corn when in competition with weeds. Cultivars AG 1051 and BRS 106 were grown with (two hoeings, at 20 and 40 days after sowing) or without weed control. In order to evaluate crop growth, six collections of the above-ground part and the root system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…In the same comparison, we found greater competitiveness in the corn hybrids Syngenta Status VIP3, Pioneer P1630H, Pioneer 30F53 YH, and Dow 135021, which presented smaller losses of grain productivity in contrast to the other hybrids. Some studies have evidenced differences in the competitive ability of corn hybrids in the presence of weeds, a fact assigned to several factors, mainly the competition that occurs among the species involved, be it intra-or interspecific (BRITO et al, 2011;SILVA et al, 2011;FARIA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same comparison, we found greater competitiveness in the corn hybrids Syngenta Status VIP3, Pioneer P1630H, Pioneer 30F53 YH, and Dow 135021, which presented smaller losses of grain productivity in contrast to the other hybrids. Some studies have evidenced differences in the competitive ability of corn hybrids in the presence of weeds, a fact assigned to several factors, mainly the competition that occurs among the species involved, be it intra-or interspecific (BRITO et al, 2011;SILVA et al, 2011;FARIA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this study showed that less productive materials presented higher competitive ability with U. plantaginea, considering the parameter i, quite possibly due to a smaller need for allocating resources in other organs of the plant rather than the ear. Leaf architecture and plant arrangement are factors that influence the absorption of solar radiation and the performance of photosynthesis, elements that have a direct relationship with the development of ears and grains (BRITO et al, 2011;SILVA et al, 2011;FARIA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Üretim alanlarında sorun olan yabancı ot türleri, mısır üretiminde % 37'lik bir ürün kaybına neden olabilmektedirler [6]. Mısırda, yabancı otlarla mücadele dönemi iki aylık süreci kapsamaktadır [7]. Bu süreçte verim kayıplarının önüne geçilmesi için mücadelenin doğru yönetilmesi ve etkin bir şekilde yapılması gerekmektedir.…”
Section: Introductionunclassified